DEVELOPMENT AND VALIDATION OF STABILITY-INDICATING HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHIC METHOD FOR BUDESONIDE - DAMLE, MRINALINI CHINTAMANI; DILIP MESHRAM, PRATIMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: A stability-indicating high-performance thin-layer chromatographic method has been developed for budesonide. Methods: Chromatographic separation was achieved on aluminum plates pre-coated with silica gel 60 F254 as the stationary phase using ethyl acetate: toluene (7:3) v/v as the mobile phase. The densitometric evaluation was carried out at 246 nm. The developed method of stability-indicating was validated as per the ICH Q2 (R1) guidelines. Stress degradation studies such as hydrolysis under different pH conditions, photolytic degradation, thermal degradation, and oxidative degradation were performed as per ICH Q1A (R2) and Q1B guidelines. Results: The Rf value of budesonide was found to be 0.48±0.03. The response in terms of peak area was linear over the concentration range of 500–2500 ng/band, with the regression coefficient value greater than 0.99. The LOD and LOQ were 28.04 ng/band and 84.96 ng/band, respectively. Conclusion: This method can conveniently be used for quantitative analysis of budesonide on a routine basis.